2017
DOI: 10.1007/s13197-017-2629-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lactic acid bacteria from traditional pickles of Himachal Pradesh, India

Abstract: A total of 15 isolates of lactic acid bacteria (LAB) were isolated from traditional pickles of rural and urban areas of Himachal Pradesh. These isolates were identified as (7), (3), (2), (1), (1) and sp. (1) on the basis of morphological, biochemical and 16S rDNA sequence analysis. All the LABs produced exopolysaccharides, have antibiotic susceptibility, and possess activity of β-galactosidase, β-glucosidase, protease and amylase, while none of the isolates showed haemolytic activity. Out of 15 isolates tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 24 publications
6
53
0
4
Order By: Relevance
“…Other studies have reported the presence of the same species of non-starter LAB on spontaneously fermented food of different origins and natures. L. plantarum occurs with high frequency in different fermented vegetables around the world such as brined olives ( 28 , 31 ), sauerkraut ( 32 ), and pickles ( 4 , 5 , 26 , 30 ). L. rhamnosus niches are more diverse, with probiotic strains originating from the human intestine ( 33 ) and other relevant isolates obtained from cheese ripening ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported the presence of the same species of non-starter LAB on spontaneously fermented food of different origins and natures. L. plantarum occurs with high frequency in different fermented vegetables around the world such as brined olives ( 28 , 31 ), sauerkraut ( 32 ), and pickles ( 4 , 5 , 26 , 30 ). L. rhamnosus niches are more diverse, with probiotic strains originating from the human intestine ( 33 ) and other relevant isolates obtained from cheese ripening ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to different stressful conditions, such as high salt concentrations, development at acidic pH and growth at high or low temperatures, are also considered as selection criteria for the development of starters for the food industry. Vegetables are an important niche for the isolation and selection of LAB for starter and probiotic applications ( 4 , 5 ). The fermented plants most widely consumed around the world include olives, cucumbers and cabbage, and to a lesser extent carrots, beets and peppers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the L. mesenteroides identified, CAL14 had the best antimicrobial profile since it inhibited the growth of B. cereus , L. monocytogenes (Strongly), L. lactis , F. oxysporum , S. cerevisiae , and C. tropicalis . It is also common to isolate strains of L. mesenteroides , which is capable of growth inhibition of L. monocytogenes [ 5 , 12 , 14 , 34 ] or B. cereus [ 35 ]. E. mundtii and L. mesenteroides isolates from the present report did not inhibit the growth of S. aureus , E. coli , or S .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory activity of LAB has been widely reported ( Table 3). LAB strains were isolated from samples of traditional pickles taken from rural and urban areas of Himachal Pradesh, and all isolates showed antimicrobial activity against Bacillus cereus, Escherichia coli, Staphylococcus aureus, and Shigella dysenteriae (Monika et al, 2017). Also, LAB with antimicrobial capacity has been isolated from a traditional fermented milk and corn product (Ahlberg et al, 2016).…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%